Dynamics of a sprayer with large flexible boom - Gofron, Marian (Computer Assisted Methods in Engineering and Science, 2023)
The quality of spraying chemicals in a field depends on the distance between the boom of the sprayer and the canopy. Keeping that distance relatively constant enables even distribution of chemicals over the field. However, because the boom has a significant moment of inertia due to its length, (commonly 30 [m] and above) the vehicle has a tendency to roll. The excessive rolling significantly decreases the quality of spraying and can even cause damage to the boom if the tip of the boom hits the ground. The boom itself deflects significantly due to its flexibility and can increase the total amplitude of the boom tip point movement during spraying operation. In this study the effect of the boom flexibility on vehicle rolling, boom rolling and boom reaction forces is evaluated. Also the effect of number of modes selected to represent flexible model, on the boom tip point deflection is analyzed. The simulation model of the sprayer is developed in DADS multibody code and mode shapes of the boom are obtained from I-DEAS code. The simulation model of the sprayer is driven over a ramp and a numerical representation of the NATC (Nevada Automotive Test Center) track.